Guidelines and legal ecosystem for the creation of Islamic content in Malaysia: towards consumer empowerment = Garis panduan dan ekosistem undang-undang bagi penciptaan kandungan kreatif Islam di Malaysia: mendepani pemberdayaan pengguna - Ali, Adibah; Abdul Ghani Azmi, Ida Madieha; Ismail, Suzi Fadhilah; Daud, Mahyuddin; Alavi, Rokiah (International Islamic University Malaysia, 2018)
The contents of creative industry must portray the cultural and religious values of the country. As a tool of nation building, creative industry plays a fundamental role in inculcating good values and the avoidance of social illnesses. The objective of this study is to examine the importance and growth of Islamic contents in Malaysian creative industry. By employing qualitative research methods, namely, content analysis and interviews, the study found that there is increase in the demand for Islamic contents. This study intends to highlight some of the concerns raised by both producers and consumers of creative content with the hope of empowering consumers in choosing content that is more suitable to their cultural and religious needs. For the Islamic content industry to flourish, having a supportive legal eco-system is imperative. This study explores the existing guidelines on Islamic content as a well as relevant legislation that governs content creation in Malaysia. The study concludes with some policy recommendations that would assist in harnessing the creation of Islamic content in Malaysia.